α, ω-Oxyfunctionalization of C12 alkanes via whole-cell biocatalysis of CYP153A from Marinobacter aquaeolei and a new CYP from Nocardia farcinica IFM10152 - Park, Hyun A.; Choi, Kwon Young (Biochemical Engineering Journal, 2020)
Medium-chain α,ω-alkanediols are extensively used as monomers in the polymer and chemical industries, with most α,ω-alkanediol production dependent on chemical processes. Here, a new bioprocess, cytochrome P450 monooxygenase (CYP) dependent whole-cell biotransformation, was investigated for use in dodecane oxidation. Escherichia coli cells over-expressing CYP153A33 from Marinobacter aquaeolei VT8 and Nfa22290 from Nocardia farcinica IFM10152 (NFA) in combination with the putida ferredoxin reductase and ferredoxin (CamA/B) redox system from Pseudomonas putida and FadL, a long-chain fatty acid transporter, were examined for dodecane and 1-dodecanol whole-cell biotransformation, respectively. It was found that the co-expression of FadL with CYP153A33 facilitated the uptake of 1-dodecanol through the cell membrane, which resulted in a five-fold increase in 1,12-dodecanediol production compared to production without a transporter. In addition, the dependence of heme precursors 5-aminolevuleic acid (ALA) and iron on 1,12-dodecanediol production was investigated and resulted in 143 mg/L of 1,12-dodecanediols production at 0.5 mM ALA and 0.1 mM FeSO4 concentrations. Finally, 0.88 mM (178 mg/L) and 1.7 mM (346 mg/L) of 1,12-dodecanediols were produced (∼8.5 % conversion) through the whole-cell biotransformation of 20 mM 1-dodecanol using CYP153 and Nfa22290, respectively.
Keywords: CYP153A33; Marinobacter; Nfa22290; Nocardia; Whole-cell biotransformations; CYP153A33; Marinobacter aquaeolei; Nfa22290; Nocardia farcinica IFM10152; Whole-cell biotransformation; α,ω-Dodecanediol